2011
DOI: 10.1111/j.1442-200x.2011.03350.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antithrombin III treatment in vascular injury model of mice

Abstract: Our results suggested that a high dose of ATIII may influence the sequelae of arterial injury by reducing mural thrombus formation and limiting the inflammatory reaction of the vessel wall without altering the process of vascular remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Studies have previously reported that the occurrence and development of certain cancers was also closely associated with SERPINC1; Zietek et al (22,23) reported increased levels of ATIII in the serum of patients with kidney cancer and the tumor tissues of patients with bladder cancer. Other studies observed that SERPINC1-encoded proteins exhibited inhibitory effects on angiogenesis and suppressed proliferation (24,25). To the best of our knowledge, the role of SERPINC1 in the occurrence and development of NPC has not been investigated.…”
Section: Introductionmentioning
confidence: 93%
“…Studies have previously reported that the occurrence and development of certain cancers was also closely associated with SERPINC1; Zietek et al (22,23) reported increased levels of ATIII in the serum of patients with kidney cancer and the tumor tissues of patients with bladder cancer. Other studies observed that SERPINC1-encoded proteins exhibited inhibitory effects on angiogenesis and suppressed proliferation (24,25). To the best of our knowledge, the role of SERPINC1 in the occurrence and development of NPC has not been investigated.…”
Section: Introductionmentioning
confidence: 93%
“…It inhibits thrombin and other serine proteases generated by the coagulation cascade. High-dose ATIII has been shown to have a strong anti-inflammatory effect in mouse models of endothelial damage, such as DIC and I/R injury [60]. …”
Section: Atiii As a Potential Treatment For Kidney-related Diseasesmentioning
confidence: 99%
“…ATIII can not only inactivate thrombin and other serine proteases in the coagulation cascade, but also suppress the inflammatory response of the immune system [67,68]. Maeda et al [60] showed that high-dose ATIII alters the consequences of vascular injury by reducing mural thrombus formation and limiting the inflammatory reaction of the vessel wall, without exerting a prolonged inhibitory effect on positive vascular remodeling. The treatment with ATIII reduces inflammatory cell infiltration, as determined by the CD11b + cell density in the adventitial area.…”
Section: Atiii As a Potential Treatment For Kidney-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Antithrombin alters microvasculature cellular interactions and improves recovery from tissue injury in animal models of ischemia-reperfusion, acute lung injury, and sepsis. [12][13][14][15][16] Indeed, post-TBI AT-III therapy reduces in vivo penumbral neurovasculature recruitment of circulating leucocytes while mitigating both local microvascular permeability and cerebral edema. 11 While this work offers the promise of acute functional recovery in injured animals, it is unknown if AT-III affects post-TBI cognitive recovery weeks after injury.…”
mentioning
confidence: 99%